2010
DOI: 10.1097/bcr.0b013e3181cb8cb8
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Fluid Requirements in Toxic Epidermal Necrolysis?

Abstract: Acute fluid requirements in toxic epidermal necrolysis (TEN) have neither been quantified nor reported. The purpose of this study was to examine acute fluid administration in TEN patients. A consecutive series of criteria and biopsy-confirmed cases of TEN admitted to our burn centre were selected for retrospective analysis. Charts were reviewed for demographic and resuscitation variables for the first (D0), second (D1), and third (D2) 24-hour periods after burn center admission. Twenty-one TEN cases were avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Age has been previously reported as a factor associated with mortality for TEN patients, consistent with many other studies [12,14,15,18]. Interestingly, in our series, TBSA% was not significantly different between survivors and non-survivors, which is in keeping with some studies [14,15,18], but conversely at odds with others that have shown a strong association between TBSA% and mortality [4,13,15].…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Age has been previously reported as a factor associated with mortality for TEN patients, consistent with many other studies [12,14,15,18]. Interestingly, in our series, TBSA% was not significantly different between survivors and non-survivors, which is in keeping with some studies [14,15,18], but conversely at odds with others that have shown a strong association between TBSA% and mortality [4,13,15].…”
Section: Discussionsupporting
confidence: 38%
“…Whilst mortality rates for TEN patients has been reported widely, the percentage of patients that died of 37% was similar to current trends, which have suggested that 30-40% mortality was commonplace with advances in critical care management of patients afflicted with burn-like diseases, introduction of intravenous immunoglobulin and standardised TEN treatment protocols [4,12,13,14,15,16]. This notwithstanding, mortality rates >40% have been reported, even in the last decade [17].…”
Section: Discussionmentioning
confidence: 98%
“…The initial administration of 2 mL/kg/% affected body surface area of intravenous crystalloids is usually sufficient to ensure adequate urine output and correct hypotension. 4 Additional nutritional requirements result from the loss of nitrogen and energy from the wound exudate, the hypermetabolic response of TEN and sepsis and the promotion of wound healing. However, these requirements may be lower than in burns, with one paediatric study suggesting that patients with TEN require 22% fewer calories per day than patients with burns.…”
Section: Supportive Carementioning
confidence: 99%
“…The unit has expertise in providing analgesia, maintaining fluid and electrolyte balance and preventing and treating superinfection. It has been recently noted that in contrast to burns, TEN affects the epidermis and hence fluid and electrolyte requirements are less than for burns of the same extent [121]; initial administration of 2 ml/kg/%TBSA is usually sufficient [122]. Additional nutritional requirements result from loss of nitrogen and energy from the wound exudate, the hypermetabolic response of TEN and sepsis and the promotion of wound healing.…”
Section: Supportive Carementioning
confidence: 99%